ESTIMASI PARAMETER PENDIDIKAN KESEHATAN MASYARAKAT HASIL INTERVENSI COOPERATIVE SELF HELP DI PROVINSI DIY - Herawati, Lucky (Universitas Negeri Yogyakarta, 2010)
Pre-post test with control group experimental research design, applied on 30 dasa wisma groups in 3 public health center work areas of Bantul regency, with main purpose to find out the estimation number of parameter of public health education as a result of cooperative self help intervention and to construct the model which suitable for dasa wisma woman, resulting: a) Action aspect shows the highest estimation number is 0,73, and b) Model of cooperative self-help approach is suitable to be applied on dasa wisma